2014
DOI: 10.1088/1758-5082/6/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Laser cell-micropatterned pair of cardiomyocytes: the relationship between basement membrane development and gap junction maturation

Abstract: The basement membrane (BM), a network of laminin and collagen IV, mechanically supports individual cells and directly mediates cell-cell and cell-extracellular matrix (ECM) interactions. For example, the BM network that tightly encloses each cardiomyocyte (CM) mediates the alignment of CMs with collagen I in the ECM. Additionally, the BM-laminin is involved in the formation of gap junctions (GJs), which regulate electrical coupling between two CMs in the myocardium. The role of BM in GJ maturation remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Neonatal ventricular CMs were harvested from the rats using a two-day protocol. The detailed procedure is described in our previous publications 38 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Neonatal ventricular CMs were harvested from the rats using a two-day protocol. The detailed procedure is described in our previous publications 38 39 .…”
Section: Methodsmentioning
confidence: 99%
“…It is known that cell-cell junctions are features of decidua establishment and function as macromolecular barriers between the mother and embryo which can block penetrance of IgG that can elicit unwanted immune rejection of the embryo and add rigidity to the tissue [86,87]. Interestingly, a recent study on cardiomyocytes, a mesenchymal-derived cell encapsulated by BM, showed a similar pericellular BM that underwent alterations for the mediation of cell junction formation [88]. Perhaps decidua BM also mediates tight junction formation and functions as an additional selective barrier and contributes to rigidly while junctions are established.…”
Section: Discussionmentioning
confidence: 99%
“…One such is the use of laser tweezers for single-cell micropatterning. A study utilized this technology to prepare the pattern and identify interactions between CMs, specifically at their gap junctions ( Yang et al., 2014a ). These laser etching techniques offer the unique ability to fabricate cardiac tissue structure with high degrees of resolution both consistently and efficiently through the vaporization of the material ( Gittard and Narayan, 2014 ).…”
Section: Engineering Methods For Fabricating Cardiac Engineered Const...mentioning
confidence: 99%
“…They contain sarcolemma for anchoring the integrin and receptor transmembrane proteins that bind the CM to the extracellular matrix (ECM), including cardiac basement membrane ( Allyson Walker and Francis Spinale, 1999 ; Yang et al., 2015 ). The cardiac basement membrane plays key roles in sarcomerogenesis, CM-CM interaction, and cardiac electrophysiology based on the findings in our previous engineering models ( Yang et al., 2014b ; Yang et al., 2014 ; Yang et al., 2015 ). The sarcoplasmic reticulum in CMs stores the Ca 2+ used in the excitation-contraction coupling ( Williams, 1997 ).…”
Section: Cell Types In Heartmentioning
confidence: 98%